Sensory constraints on prey detection performance in an ensemble of vespertilionid understorey rain forest bats - Hashim, Rosli; Siemers, B.M.; Schmieder, D.A.; Kingston, T. (2012)
1. Bats evolved different strategies to find prey close to vegetation. Previous studies on European bats of the genus Myotis (Vespertilionidae) revealed an association between echolocation call bandwidth and the ability to find and capture prey close to vegetation. Here, we investigated whether the role of call bandwidth in prey detection is a more general principle in bat sensory ecology. We focused on eight palaeotropical species of the vespertilionid subfamilies Kerivoulinae and Murininae, as they also achieve very broad bandwidths with the first harmonic of their echolocation calls. 2. All species emitted calls of bandwidths broader than 90kHz with extremely high start frequencies (max. 230kHz), and all of five experimentally tested species were able to catch prey closer than 6cm, occasionally even closer than 2.5cm, to a standardized vegetation-like background. The performance and call data corroborate the hypothesis that bats with very broadband calls and high-frequency components have access to prey very close to vegetation and establish this as a more general principle in bat sensory ecology. 3. In a second experiment, we questioned whether echolocation is the only sensory cue used by the bats to find prey. Echo-acoustic prey dummies that did not smell or taste like arthropods and did not produce any sounds or movement were presented to all five species. In 80 of 83 cases, the bats caught or attempted to catch the dummy, indicating that the bats used only echo-acoustic information for prey detection and recognition in our experiments. 4. We then tested whether the sensory difficulty in finding prey close to clutter constrains the bats' attacks on prey or whether flight manoeuvrability may be limiting by manipulating the echo reflection properties of the background. The bats were able to find prey very slightly, but significantly closer to a background with lower echo reflection (an easier sensory task), which corroborates the limiting role of sensory performance. 5. While silent, motionless prey close to and in vegetation will be accessible to these specialists, it will go undetected by other bats. This scenario supports the idea that sensory specialization mediates resource access and niche separation (sensory niche partitioning).